Lactic Acid Bacteria – A Promising Tool for Controlling Chicken Campylobacter Infection - Wyszyńska, Agnieszka Krystyna; Godlewska, Renata (Frontiers in Microbiology, 2021)
Since 2005, campylobacteriosis is the most common zoonotic disease in Europe. The main reservoir of pathogenic Campylobacter strains are broilers, which makes raw and undercooked poultry meat two major sources of disease. Infection in chicken flocks is most often asymptomatic, despite a high level of colonization reaching 106-109 cfu / g in animal ceca. It is widely believed that controlling the level of colonization of the birds’ digestive tract by pathogenic strains is a good way to increase food safety. Many treatments have been proposed to combat or at least reduce the level of colonization in animals reservoirs: probiotics, bacteriophages, vaccines, and anti-Campylobacter bacteriocins. This review focuses on the effects of Campylobacter infection on chicken microbiome and colonization control strategies using probiotics (mostly lactic acid bacteria, LAB), which are live microorganisms included in the diet of animals as feed additives or supplements. Probiotics are not only an alternative to antibiotics, which were used for years as animal growth promoters, but they also constitute an effective protective barrier against excessive colonization of the digestive system by pathogenic bacteria, including Campylobacter. Moreover, one of the many beneficial functions of probiotics is the ability to manipulate the host's microbiota. Recently, there have also been some promising attempts to use lactic acid bacteria as a delivery system of oral vaccine against Campylobacter. Recombinant LAB strains induce primarily a mucosal immune response against foreign antigens, accompanied by at most a low-level immune response against carrier strains. Since the main barrier against invasion of pathogens in the gastrointestinal tract is the intestinal mucosal membrane, the development of effective oral vaccines to protect animals against enteric infection is very reasonable.